QUALITY ASSURANCE SYSTEM OF THE UNIVERSITY EDUCATION IN AUSTRIA - Mukan, Nataliya; Shyika, Oksana; Shyika, Julia (Mountain School of Ukrainian Carpaty, 2020)
The article deals with the analysis of specificity of modern quality assurance system of the university education in Austria based on the historical and pedagogical research. According to the aim and objectives of the research, the authors used theoretical and applied research methods (descriptive, statistical, comparative, analytical, generalisation, interpretation, logical, structural, systemic methods, induction, deduction; interviews, polls, questioning). In the article, the methodology of the analysis of education quality assurance in Austrian universities has been presented. The authors highlight theoretical and methodological fundamentals of the process of quality assurance of the university education in the country under research. The authors analyse quality assurance of the university education in Austria according to the structural and functional model. This model comprises conceptual (concepts that underlie the quality assurance of university education), goal setting (goals and plan for their implementation), instrumental (mechanisms: professional, educational and cultural standards, system of conferring of educational qualification levels and scientific degrees; quality management; accreditation, assessment, ISO standards, overall quality management) and assessing components. It has been found out that the system of quality assurance of university education in Austria is being implemented in three stages: programming (analysis of the current situation, adopting of fundamental standards, clear definition of quality, its purpose, activity directions, choice of tools), implementation (choice of mechanisms, standards, ways of quality assurance, quality management; ISO standards, overall quality management, spheres of implementation (R&D, academic process, internal services, professional development of employees), evaluation (programs, evaluation techniques, indicators of success; types of evaluation (indirect, traditional, non-traditional, content-oriented, organizational and structural). The authors present the classification and characteristics of university education quality research resources in Austria. They characterise the contemporary tendencies of the development of the system of university education quality assurance as well as analyse and compare European and Austrian qualification standards. The authors present conclusions and substantiate the necessity for further studies.